Assessing contexts of learning: an international perspective - Kuger, Susanne; Klieme, Eckhard; Jude, Nina; Kaplan, David (Springer International Publishing, 2017)
Foreword -- The Present Volume -- Preface -- Contents -- Part I: Introduction -- Chapter 1: Dimensions of Context Assessment -- 1.1 Introduction -- 1.2 Learning in Contexts Worldwide -- 1.2.1 Taxonomies of Topics and Constructs -- 1.2.2 Common Content Areas -- 1.2.2.1 Education Outcomes -- 1.2.2.2 Student Background -- 1.2.2.3 Teaching and Learning Processes -- 1.2.2.4 School Policies and Governance -- 1.3 Expansion of the Common Content -- 1.3.1 Rationale for Expansion -- 1.3.2 Expanding Target Groups -- 1.3.3 Expanding the Student Sample -- 1.3.4 Expanding Available Data Sources
Description based upon print version of record
Keywords: Electronic books